Social media political campaign model of local elections in Pelalawan Regency Riau - Fatmawati Moekahar; Fitria Ayuningtyas; Fitri Hardianti (Jurnal Kajian Komunikasi, 2022)
The modern rise of social media has altered the strategies used in political campaigns. Compared to traditional advertising, social media may lower the cost of a campaign. The Zukri-Nasar team effectively used social media for political campaigns for the 2020 local elections in Pelalawan Regency, Riau. Social media generated 30% of the vote because it can spread messages rapidly, widely, and interactively. Political actors utilize social media to develop their self-image. This study is descriptive-qualitative, and the sampling method used was purposive sampling. The informants comprised seven important informants who were part of the winning side in the municipal election in Pelalawan. An informant is someone with reliable knowledge regarding a political campaign. According to the study, Facebook is the most widely used platform for political campaigns because it is the most popular social networking platform in Pelalawan Regency, Riau. Political advertisements featuring 3D caricatures and political orientation are used as social media political campaign techniques. This tactic is a component of a unique, awareness-raising, and personal branding campaign. The candidate’s personal character is presented as accurately as possible on their social media campaign. Furthermore, the political campaign model found in the research was called The Integrative and Collaborative Model of the political campaign.